Role of G protein-coupled receptors in inflammation - Sun Lei; Ye Richard D (Acta Pharmacologica Sinica, 2016)
G protein-coupled receptors (GPCRs) play important roles in inflammation. Inflammatory cells such as polymorphonuclear leukocytes (PMN), monocytes and macrophages express a large number of GPCRs for classic chemoattractants and chemokines. These receptors are critical to the migration of phagocytes and their accumulation at sites of inflammation, where these cells can exacerbate inflammation but also contribute to its resolution. Besides chemoattractant GPCRs, protease activated receptors (PARs) such as PAR1 are involved in the regulation of vascular endothelial permeability. Prostaglandin receptors play different roles in inflammatory cell activation, and can mediate both proinflammatory and anti-inflammatory functions. Many GPCRs present in inflammatory cells also mediate transcription factor activation, resulting in the synthesis and secretion of inflammatory factors and, in some cases, molecules that suppress inflammation. An understanding of the signaling paradigms of GPCRs in inflammatory cells is likely to facilitate translational research and development of improved anti-inflammatory therapies.